Persistent testicular delta5-isomerase-3beta-hydroxysteroid dehydrogenase (delta5-3beta-HSD) deficiency in the delta5-3beta-HSD form of congenital adrenal hyperplasia. - Schneider, G (1975)
A partial testicular defect in testosterone secretion has been documented in a pubertal male with a congenital adrenal hyperplasia due to hereditary deficiency of the delta5-isomerase-3beta-hydroxysteroid dehydrogenase enzyme complex (delta5-3beta-HSD). Diagnosis of the enzymatic defect is based on the clinical picture of ambiguous genitalia and salt-losing crisis in infancy, together with high urinary delta5-pregnenetriol and plasma dehydroepiandrosterone when the patient was taken off replacement corticoid treatment. No hormonal response to ACTH or salt deprivation was demonstrable. In addition, in vivo studies revealed a partial enzymatic defect in the testis. Although plasma testosterone was low-normal (250 ng/100 ml), plasma delta5-androstenediol was markedly elevated and rose to a greater extent than testosterone after human chorionic gonadotropin administration. In vitro testicular incubation studies suggested a testicular delta5-3beta-HSD enzyme defect with less delta4 products formed from delta5 precursors than in a control testis. Histochemical studies of the testis were also consistent with this defect. Testicular biopsy revealed spermatogenic arrest, generally diminished Leydig cells, but with focal areas of Leydig cell hyperplasia as well as benign Leydig cell hyperplasia as well as benign Leudig cell nodules within the spermatic cord. In vivo studies of steroid metabolism suggested intact peripheral or hepatic delta5-3beta-HSD activity. These studies imply that delta5-3beta-HSD activity differs in the gonad, adrenal, and peripheral organs. These findings are compatible with the concept that the enzyme complex consists of subunits and/or that enzymes in these organs are under different genetic control.